Ta có : \(A=\dfrac{bc}{\left(a-b\right)\left(a-c\right)}-\dfrac{ca}{\left(b-c\right)\left(a-b\right)}+\dfrac{ab}{\left(a-c\right)\left(b-c\right)}\)
\(=\dfrac{bc\left(b-c\right)-ca\left(a-c\right)+ab\left(a-b\right)}{\left(a-b\right)\left(a-c\right)\left(b-c\right)}\)
Đặt \(B=bc\left(b-c\right)-ca\left(a-c\right)+ab\left(a-b\right)\)
\(=b^2c-bc^2-a^2c+ac^2+a^2b-ab^2\)
\(=a\left(c^2-b^2\right)-b\left[\left(c^2-b^2\right)+\left(b^2-a^2\right)\right]+c\cdot\left(b^2-a^2\right)\)
\(=\left(c-b\right)\left(c+b\right)\left(a-b\right)-\left(a-b\right)\left(a+b\right)\left(c-b\right)\)
\(=\left(c-b\right)\left(a-b\right)\left(c-a\right)=\left(a-b\right)\left(a-c\right)\left(b-c\right)\)
\(\Rightarrow A=\dfrac{\left(a-b\right)\left(b-c\right)\left(a-c\right)}{\left(a-b\right)\left(b-c\right)\left(a-c\right)}=1\)
Vậy A=1